AGE AND GROWTH IN THE CATFISH TACHYSURUS TENUISPINIS (DAY) - Dan, S S (Indian Journal of Fisheries, 2011)
Both the species of catfishes viz., T. tenuispinis and T. thdassirms form important fisheries along the Andhra, Orissa and West Bengal coasts contributing about 20.8% of the demersal fish catches (Sekharan 1973a, & b). Maturity, fecundity and spawning (Dan 1976); length-weight relationship (Dan and Mojumder 1975) and the food and feeding (Mojumder and Dan, MS) of the species have been studied. Pectoral spines in a few catfishes (Pantulu 1961, 62) were used in the study of their age and growth. The present paper deals with the study of age and growth with the help of opercular bones, otoliths and lengtii-frequency data in the catfish, T. tenuispinis.